DNA binding of the Bordetella pertussis H1 homolog alters in vitro DNA flexibility. - Zu, T (1996)
BpH1, the Bordetella pertussis H1 homolog, interacts with chromosomal DNA. With DNase I protection assays, we demonstrate in this study that BpH1 binds DNA in a nonspecific manner and that it may cover DNA fragments from end to end. Although the binding was shown to be nonspecific, preferential binding sites and sites resistant to BpH1 binding were identified within and upstream of the pertussis toxin promoter sequence. In the presence of DNA ligase, BpH1 favored the formation of multimeric DNA fragments of various sizes and prevented ring closures, suggesting a diminished flexibility of the DNA fragments and thus indicating that BpH1 acts as a macromolecular crowding agent.